Intergenerational Transfers, Lifetime Welfare and Resource Preservation - Simone Valente (ETH Zurich, CER-ETH - Center of Economic Research, 2006)
This paper analyzes overlapping-generations models where natural capital is owned by selfish agents. Transfers in favor of young agents reduce the rate of depletion and increase output growth. It is shown that intergenerational transfers may be preferred to laissez-faire by an indefinite sequence of generations: if the resource share in production is sufficiently high, the welfare gain induced by preser- vation compensates for the loss due to taxation. This conclusion is reinforced when other assets are available, e.g. man-made capital, claims on monopoly rents, and R&D investment. Transfers raise the welfare of all generations, except that of the first resource owner: if resource endowments are taxed at time zero, all successive generations support resource-saving policies for purely selfish reasons.
Keywords: H30; Q01; Q20; 330; Distortionary Taxation; Intergenerational Transfers; Overlapping Generations; Renewable Resources; Sustainability; Technological Change; Intergenerationale Übertragung; Generationengerechtigkeit; Natürliche Ressourcen; Erneuerbare Ressourcen; Nachhaltige Entwicklung; Technischer Fortschritt; Overlapping Generations; Theorie